Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.